2011
DOI: 10.1016/j.neuropsychologia.2010.09.028
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal structure or function of the amygdala is a common component of neurodevelopmental disorders

Abstract: The amygdala, perhaps more than any other brain region, has been implicated in numerous neuropsychiatric and neurodevelopmental disorders. It is part of a system initially evolved to detect dangers in the environment and modulate subsequent responses, which can profoundly influence human behavior. If its threshold is set too low, normally benign aspects of the environment are perceived as dangers, interactions are limited, and anxiety may arise. If set too high, risk taking increases and inappropriate socialit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
132
0
4

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 159 publications
(140 citation statements)
references
References 252 publications
(279 reference statements)
4
132
0
4
Order By: Relevance
“…Amygdala function is of high interest for cognitive, social and psychiatric neuroscience, emphasizing the need for reliable assessments in humans (Adolphs, 2010;Sander et al, 2003;Schaefer and Gray, 2007;Schumann et al, 2011). In a previous study we have compared the retest reliability of three different tasks (emotional, motivational and cognitive) comprising an fMRI task battery (Plichta et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Amygdala function is of high interest for cognitive, social and psychiatric neuroscience, emphasizing the need for reliable assessments in humans (Adolphs, 2010;Sander et al, 2003;Schaefer and Gray, 2007;Schumann et al, 2011). In a previous study we have compared the retest reliability of three different tasks (emotional, motivational and cognitive) comprising an fMRI task battery (Plichta et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The amygdala is a phylogenetically conserved structure, in evolutionary terms predating the neocortex, and consists of a number of nuclei (Schumann et al, 2011;Stephan & Andy, 1982). In humans, these nuclei may be placed into two main groups according to anatomy and neuronal substrate contained: centromedial and corticobasolateral (Stephan & Andy, 1982).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, postoperative imaging demonstrates the surgical lesion to be the widest at its medial edge, tapering as it extends. This suggests potentially greatest impact on medially located nuclei (for an anatomical depiction of relevant nuclei, the reader is referred to Figure 2 of Schumann, Baumann, and Amaral (2011)) and may provide additional insight into distinct functions of amygdaloid structures. We present the case history, methods of assessment and results, and review studies supporting the amygdala's role in specific phobia.…”
Section: Introductionmentioning
confidence: 99%
“…Across a range of studies investigating neurodevelopmental disorders, there is evidence of amygdala dysregulation from postmortem studies, structural MRI analyses, and functional MRI [50].…”
Section: Amygdalar Models Of Neurological and Neuropsychiatric Disordmentioning
confidence: 99%
“…Schumann et al [50] conducted a study where autistic adults showed a decrease in neurons in the amygdala compared to control groups. It appears that the amygdala undergoes an abnormal pattern of postnatal development that includes unusual enlargement, followed by a reduction of amygdala size, or decreased neurons, into adulthood.…”
Section: The Amygdala -A Discrete Multitasking Manager 294mentioning
confidence: 99%